To find the equivalent expression for \(-64\), let's evaluate each of the given options:
-
\(2^3 \cdot 2^2 \cdot 2^0\):
- Calculate this expression:
- \(2^3 = 8\)
- \(2^2 = 4\)
- \(2^0 = 1\)
- Combine them:
- \(8 \cdot 4 \cdot 1 = 32\)
- So, this expression is \(32\), not \(-64\).
- Calculate this expression:
-
\(4^{-3}\):
- Rewrite this using the property of exponents:
- \(4^{-3} = \frac{1}{4^3} = \frac{1}{64}\)
- So, this expression is \(0.015625\), not \(-64\).
- Rewrite this using the property of exponents:
-
\(-2^{-2} \cdot (2^8)\):
- Calculate \(-2^{-2}\):
- \(-2^{-2} = -\frac{1}{2^2} = -\frac{1}{4}\)
- Calculate \(2^8\):
- \(2^8 = 256\)
- Now multiply:
- \(-\frac{1}{4} \cdot 256 = -64\)
- Calculate \(-2^{-2}\):
Thus, the expression that is equivalent to \(-64\) is \(-2^{-2} \cdot (2^8)\).